Efektivitas Prestasi Belajar Pendidikan Agama Islam Dalam Penerapan Strategi Pembelajaran Berbasis Paikem Guna Mewujudkan Merdeka Belajar - Mardhiyah Agung W (Journal on Education, 2024)
This study aims to determine the development of education in Indonesia has experienced significant progress, especially in the field of Islamic education. The government has taken steps to develop the sector, including regulations and the National Curriculum to set national education standards in Indonesia. The National Curriculum focuses on developing skills and character that can create young people based on the PAIKEM (Active, Innovative, Creative, Effective, and Fun) approach. This research focuses on SD Negeri Dukuh 02 Mojolaban, a formal school located in Geblug, Mojolaban District, Sukoharjo Regency, Central Java Province. The methodology of this study included qualitative research, which aimed to collect data on the quality and performance of Islamic education in schools. This method includes the collection of documentation data and physical data, as well as the collection of qualitative data through interviews with school officials, academics, and teachers. Observational data collection includes observation of the school environment, student participation, student activities, learning process, and what factors need to be considered when collecting data. The implementation of the PAIKEM strategy at SD Negeri Dukuh 02 Mojolaban aims to achieve student achievement. The PAIKEM strategy focuses on creating a conducive learning environment that encourages students to excel in learning.